Integration of Philosophical Values in Human Relations Management: Systematic Literature Review - Esvanti, Mirza; Nafisah, A’isy Fikli; Winarno, Agung (Economics and Business Journal (ECBIS), 2025)
Human relations management is an important aspect of an organization's success, especially in creating a harmonious, productive, and ethical work environment. This study aims to explore the integration of philosophical values in human relations management through the Systematic Literature Review (SLR) approach. The Systematic Literature Review (SLR) method was used in this study to analyze and synthesize various previous studies related to human relations management. The SLR process involves identifying, screening, and evaluating studies from a variety of sources, including international indexed journals, to gain an in-depth understanding of key trends and issues in the implementation of humanitarian relations management. Of the 150 articles found, 52 articles met the inclusion criteria for further analysis. By analyzing the literature from various academic databases, this study identifies key concepts in philosophy, such as humanism, deontological ethics, utilitarianism, and existentialism, that are relevant to support the management of interpersonal relationships in organizations. The results of the study show that the application of philosophical values can improve the quality of relationships between individuals through more ethical decision-making, value-oriented leadership, and strengthening mutual respect in work interactions. In addition, this study reveals a significant gap in the literature related to the practical implementation of philosophy in the context of modern management, especially in certain sectors. These findings make a theoretical contribution in expanding the understanding of the role of philosophy in human relations management as well as offering recommendations for further research and practical applications in organizational environments.